COVID-19 Vaccine Concerns and Acceptability by Language in a Marginalized Population in Rhode Island. (December 2021) - Bloom, Molly; Verma, Shelly; Ram, Deepika; Roberton, Timothy; Pacheco, Cristina; Goldman, Roberta E.; Lima, Kevin; Faith Vera Cruz, Maxine; Szkwarko, Daria
Introduction: We need to understand the continued concerns and acceptability of COVID-19 vaccines within marginalized communities in the United States. Our study explores the concerns and acceptability of COVID-19 vaccines, by language group, at a Federally Qualified Health Center (FQHC) in Rhode Island. Methods: We conducted an exploratory, mixed data collection telephone survey in languages spoken in the community (Spanish, Cape Verdean (CV) Creole/Portuguese, and English). Participants were asked about their COVID-19 vaccination status, as well as vaccine concerns and acceptability via 9 closed-ended and 2 open-ended questions. Chi squared and multivariate analysis was used to compare concerns and acceptability across languages. Coding and immersion/crystallization techniques were used to identify qualitative data themes. Results: The overall response rate was 58%. Side effects were cited as the most frequent (66%) concern among all language groups. Concern about the speed of vaccine development, vaccine ingredients, and being in a research trial varied significantly by language. Qualitative findings included concerns about chronic medical conditions and generalized fear of vaccine safety. English speakers were the most likely to report concerns and CV Creole/Portuguese speakers were the least likely to report concerns about the vaccine. Spanish and CV Creole/Portuguese participants who were not yet vaccinated reported higher acceptability to receive the vaccine compared to English speakers, with odds ratios of 2.00 (95% CI: 1.00-4.00) and 1.27 (95% CI: 0.62-2.60), respectively. Conclusion: To mitigate the effects of the COVID-19 pandemic and prepare for future pandemics, strategies must be based on understanding the beliefs and perceptions of marginalized communities.